Global Research Trends on Building Indoor Environmental Quality Modelling and Indexing Systems—A Scientometric Review - Roumi, Soheil; Zhang, Fan; Stewart, Rodney A. (Energies (Basel), 2022)
The purpose of this study is to provide a holistic review of two decades of research advancement in the indoor environmental quality modelling and indexing field (IEQMI) using bibliometric analysis methods. The explicit objectives of the present study are: (1) identifying researchers, institutions, countries (territories), and journals with the most influence in the IEQMI topic; (2) investigating the hot topics in the IEQMI field; and (3) thematically analysing the keyword evolution in the IEQMI field. A scientometric review was conducted using the bibliometric data of 456 IEQMI research articles published in the past two decades. VOSviewer software was employed for bibliometric analysis, and the SciMAT tool was used to investigate the keywords’ thematic evolution in three sub-periods (2004–2009; 2010–2015; 2016–2021). Results show that there is a continuous increment in the number of published papers in the field of IEQMI, and 60 out of 193 countries in the world have been involved in IEQMI studies. The IEQMI research mainly focuses on: (a) thermal comfort and energy efficiency; (b) occupant satisfaction and comfort; (c) IAQ and health issues; (d) methods and procedures. This field has undergone significant evolution. While ‘indoor environmental quality was initially the only theme in the first period’, ‘occupant satisfaction’, ‘buildings’, ‘impact’, ‘building information modelling’, and ‘health’ were added as the main thematic areas in the second period; ‘occupant behaviour’ and ‘energy’ were novel themes in IEQMI studies receiving much attention in the third period.